Intra-subject replication of brain magnetic activity during the processing of speech sounds - Eulitz, C; Obleser, J; Lahiri, A (Elsevier, 2004)
The present study examined the cortical activity during processing of vocalic segments by means of whole-head magnetoencephalography (MEG) to see whether respective cortical maps are stable across repeated measurements. We investigated the spatial configuration and temporal characteristics of the N100m generators of the auditory-evoked field during the processing of the synthetic German vowels [a], [e] and [i] across 10 repeated measurements in a single subject. Between vowels, N100m latency as well as source location differences were found with the latency differences being in accordance with tonochronic principles. The spatial configuration of the different vowel sources was related to differences in acoustic/phonological features. Vowels differing maximally in those features, i.e., [a] and [i], showed larger Euclidean distances between N100m vowel sources than [e] and [i]. This pattern was repeatable across sessions and independent of the source modeling strategy for left-hemispheric data. Compared to a pure tone control condition, the N100m generators of vowels were localized in more anterior, superior and lateral parts of the temporal lobe and showed longer latencies. Being aware of the limited significance of conclusions drawn from a single case study, the study yielded a repeatable spatial and temporal pattern of vowel source activity in the auditory cortex which was determined by the distinctiveness of the formant frequencies corresponding to abstract phonological features.